Diskursus Problematika Jilbab Perspektif Yunan Yusuf Dalam Tafsir Al-Izzah - Ghoziah, Cima (Kontemplasi: Jurnal Ilmu-Ilmu Ushuluddin, 2023)
This paper will discuss Yunan Yusuf's perspective on the hijab in his interpretation of Al-Izzah while seeking answers to social issues such as women wearing the hijab still being victims of sexual harassment, the hijab being considered unfashionable by certain groups, and the hijab being seen as a hindrance to career advancement. This research is a literature-based study (library research) using a descriptive analysis method with a sociological approach. The results of this study indicate that victims of sexual harassment among women who wear the hijab have two possibilities. Yunan Yusuf explains that women who are still victims of sexual harassment may be wearing a hijab that has sexual appeal, or it could be due to men who cannot control their desires and should be advised to restrain their carnal desires to avoid seducing or disturbing women who already wear the hijab or dress according to Islamic Sharia. Furthermore, concerns of women hesitating to wear the hijab due to unfashionable reasons have been addressed with the emergence of many stores and fashion designers selling clothing that adheres to Islamic Sharia while keeping up with contemporary fashion trends. Lastly, the discussion regarding discrimination against women wearing the hijab in the workplace, leading some women to reluctantly remove their hijabs, is not justified. First, they would be violating religious rules. Second, they are protected by the law. Third, they can seek alternative employment while trusting that Allah has promised sufficiency to His faithful servants who rely on Him.